Photoprotection, photoinhibition, gene regulation, and environment - Demmig-Adams, Barbara. ((Advances in photosynthesis and respiration, including bioenergy and related processes,, 2006)
Photoprotection, Photoinhibition, Gene Regulation, and Environment examines the processes whereby plants monitor environmental conditions and orchestrate their response to change, an ability paramount to the life of all plants. "Excess light", absorbed by the light-harvesting systems of photosynthetic organisms, is an integrative indicator of the environment, communicating the presence of intense light and any conditions unfavorable for growth and photosynthesis. Key plant responses are photoprotection and photoinhibition. In this volume, the dual role of photoprotective responses in the preservation of leaf integrity and in redox signaling networks modulating stress acclimation, growth, and development is addressed. In addition, the still unresolved impact of photoinhibition on plant survival and productivity is discussed. Specific topics include dissipation of excess energy via thermal and other pathways, scavenging of reactive oxygen by antioxidants, proteins key to photoprotection and photoinhibition, peroxidation of lipids, as well as signaling by reactive oxygen, lipid-derived messengers, and other messengers that modulate gene expression. Approaches include biochemical, physiological, genetic, molecular, and field studies, addressing intense visible and ultraviolet light, winter conditions, nutrient deficiency, drought, and salinity. A random walk To and through the xanthophyll cycle -- Photoinhibition: then and now -- Future perspectives† -- Characteristics and species-dependent employment of flexible versus sustained thermal dissipation and photoinhibition -- Energy dissipation and photoinhibition: a continuum of photoprotection -- Photoinhibition and photoprotection under nutrient deficiencies, drought and salinity -- Photoinhibition and UV response in the aquatic environment -- Phosphorylation of thylakoid proteins -- Molecular analysis of photoprotection of photosynthesis -- A protein family saga: from photoprotection to light-harvesting (and back?) -- Photoprotection of photosystem II: reaction center quenching versus antenna quenching -- Photoinhibition and recovery in oxygenic photosynthesis: mechanism of a photosystem II damage and repair cycle -- Regulation by environmental conditions of the repair of photosystem II in cyanobacteria -- Photosystem I and photoprotection: cyclic electron flow and water-water cycle -- Integration of signaling in antioxidant defenses -- Signaling and integration of defense functions of tocopherol, ascorbate and glutathione -- Redox regulation of chloroplast gene expression -- Intracellular signaling and chlorophyll synthesis -- The role of peroxiredoxins in oxygenic photosynthesis of cyanobacteria and higher plants: peroxide detoxification or redox sensing? -- Lipoxygenases, apoptosis, and the role of antioxidants -- 21.